Islam di Indonesia dan Fenomena Disintegrasi Bangsa - Yusdani - (Unisia, 2003)
This article traces the problem of disintegration that emerges in Indonesia re cently. How  to solve this problem from Islamic political viewpoint? Because of this, the leaders of  muslim political organization in Indonesia should participate in solving the problem toward reformulating the theological ideas as a basis for political view and action in Indonesia, redefining the political ideas in the context of Indonesia, and to reformulate the strategy to moslem's struggle in modern Indonesia.